Features of plasma chemical etching of lithium tantalate substrate (LiTaO₃) - Fedorovich, O.A.; Hladkovska, O.V.; Hladkovskyi, V.V.; Nedybaliuk, A.F. (Вопросы атомной науки и техники, 2021)
The results of researches of plasma chemical treatment of lithium monocrystalline tantalate (LiTaO₃) from gas type, bias voltage (energy of chemically active ions) and from current of additional bias generator are given. A closed-loop electron drift plasma chemical reactor and gas mixtures containing Ar, Ar + ClС₄, and Ar + SF₆ were used for the experiments. It was found that the etching rate of LiTaO₃ for the discharge in the gas mixture Ar + CCl₄ is 14 times higher than all other mixtures that were used. It is shown that the proposed idea and approaches of LiTaO₃ processing can be effectively applied for the production of optical systems with a minimum core thickness of about 2…3 μm.